Analysis of Islamic Education Policy in the Netherlands - Aliadi, Aliadi; Helmiati, Helmiati; M. Nazir, M. Nazir (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
The purpose of this study is to analyze Islamic Education Policy in the Netherlands. The study from this study uses a literature review where the literature taken is in accordance with the subject of discussion and analyzed in depth so that conclusions and findings can be drawn in the research. Literature taken from books, journal articles, both national and international, and other literature. The result of this research is that Islamic education in the Netherlands is a complex issue that involves various challenges and opportunities. The Dutch government's policy provides space for Islamic religious education, but still emphasizes the importance of tolerance, social integration, and countering radicalization. Despite the various challenges in the implementation of this policy, with the right solutions, Islamic education can be an important instrument to support the development of an educated, tolerant and well-integrated generation of Muslims in Dutch society.